Modeling and analysis of impact of sepak takraw ball on the player's head / Iskandar - Iskandar, - (2013)
Sepak takraw is a traditional game played at the international level in Asia. The game is played using various parts of the body, except the hands. Most notably, the head is often used. Unlike soccer, no studies have yet been conducted on injuries caused by contact between the ball and the head for this sport. This research was initiated following the incidents of 24th SEA Games in Korat, Thailand, 2007, in which the Malaysian Sepak Takraw Association (PSM) had pulled out of the championship. The withdrawal was due to complains of headaches from the players believed to be caused by the sepak takraw ball used in the competition. Thus, the objectives of this research are to investigate the phenomena of ball-to-head impact and the level of the head injury on sepak takraw players, as well as to develop scalp, skull, cerebrospinal fluid (CSF) and brain model by using finite element model. The scope of this research include interviews of 100 players (questionnaire based) and data collection of ball velocity and contact positions of heading from various Sepak Takraw championships in Malaysia in 2012. The three models of heading were frontforehead, side-forehead and top-forehead impact and its effect observed on the frontalbrain and occipital-brain. Furthermore, analysis of the sepak takraw ball characteristics, drop test ball for impact on skull dummy and drop test free fall heading for validation were also conducted. The modelling and finite element analysis of the human head was further performed. The findings from the interviews revealed that after hard headings, 88% of the players experienced headaches, 64% felt emotional, 65% had tears coming out of their eyes, 68% heard droning sounds and 67% felt unbalanced. From the survey, it was found that the maximum speed of the sepak takraw ball before heading was 13.58 m/s and from simulation the maximum impact force on the head was 688.1 N, causing a maximum of brain displacement of 0.80 mm. The maximum magnitude of acceleration at the centre of gravity of the brain was found to be 1674.5 m/s2. The corresponding Head Injury Criterion (HIC) is 210.1 and the Head Impact Power (HIP) is 11.6 kW. Based on studies by Newman et. al. (2000), this implies probabilities of 42% for HIC and 39% for HIP that sepak takraw players will experience Mild Trauma Brain Injury (MTBI) from hard headings of fast speed sepak takraw balls. Therefore, this study suggests that every player should wear a head protection to reduce the impact during heading.